What drives shareholders' reaction to CEO turnovers, dividend changes, and block trades? A theoretical background - Agnieszka Preś-Perepeczo (Central European Economic Journal (CEEJ), 2023)
This study presents a review of theoretical concepts described in the literature that explain how corporate events might be perceived by investors. The theoretical discussion in this paper is related to three corporate events: CEO turnovers, dividend payouts, and block trades. The objective of this analysis is to identify and systemise the theoretical background for the drivers of shareholders' responses to these three corporate decisions. In other words, I will provide answers to the following questions: why is the market reaction sometimes positive and other times negative, and why is it sometimes stronger and other times weaker? Based on the literature review, I will show that each of the analysed corporate events might be perceived by shareholders as either positive or negative signals concerning perspectives and future cash flows. Consequently, corporate events might drive share prices up or down. However, shareholder reaction to one type of the event, such as CEO turnovers, will not always be homogeneous - only positive or negative. The strength of this reaction may also vary. The main reasons for these variations are the effectiveness of corporate governance mechanisms, investors' perceptions of the event, the event's peculiarities, and the company's characteristics, as well as other relevant circumstances and factors.
Keywords: G14; G03; M05; 330; CEO turnovers; dividend changes; block trades; market reaction; theoretical concepts